Черепица Правобережного Цимлянского городища - Моисеев, Д.А. (Хазарский альманах, 2020)
This article is about a phenomenon of tiles (tegulae and imbrexes) from the Right-Bank Tsimlyanskaya Fortress and their production technology. The deep relationship between the tile production technologies of the Right-Bank Tsimlyanskaya Fortress and the South-Western Crimea was investigated due to the detailed analysis of the technology and morphology of the material. It can bee seen in the same traces and deformations of the “rear” mode of production on Crimean and Right-Bank Tsimlyanskaya Fortress tiles. Also specifi c features were discovered that show that the Right-Bank Tsimlyanskaya Fortress tiles were made by inexperienced craftsmen. The comparison of the roasting technologies of orange-clay and gray-clay tiles allowed to formulate two important hypotheses for the history and archaeology of the site. At fi rst, a new look at the imported technology was taken by the Khazar “masters” and it was adapted to the local conditions and traditions. At second, the Right-Bank Tsimlyanskaya Fortress tiles can be divided into two chronologically different groups: the earlier from the time of the fortress construction (orange-clay) and the later from the time of the fortress lifetime (gray-clay).